The seriality dividend of American magazines - Thompson, Graham (Ohio State University Press, 2018)
This essay argues that the preconsumption cycle of material creation and supply exerted powerful effects as periodicals journeyed from paper mill to reader. So powerful were these effects that they generated a “seriality dividend,” or a return on financial and cultural investment whose impact went beyond the significance of individual or groups of periodical titles, or their content, and turned the periodical into a cultural form of such significance that it produced effects larger than the sum of its parts. Periodicals became prosperous cultural forms in the nineteenth century because their serial production generated a capacity and scale that other forms, including books, could not match. The seriality dividend consolidated the periodical as a cultural form with structural significance. Focusing on literary periodicals and their relation to literary culture more generally, this essay argues that the dividend from magazine seriality helped establish the infrastructure—the publication outlets, jobs, careers, connections, and networks—that allowed literary culture to develop in America’s major geographical centers, where the seriality dividend exerted its effects most powerfully.